As Time Goes By - Clark, Mary Higgins; Maxwell, Jan 1956-; Simon & Schuster Audio (Firm) (New York, NY Simon & Schuster Audio, 2016)
Television journalist Delaney Wright is on the brink of stardom after she begins covering a sensational murder trial for the six p.m. news. She should be thrilled, yet her growing desire to locate her birth mother consumes her thoughts. When Delaney's friends Alvirah Meehan and her husband Willy offer to look into the mystery surrounding her birth, they uncover a shocking secret they do not want to reveal.
Keywords: Women television journalists -- Fiction; Trials (Murder) -- Fiction; Family secrets -- Fiction; Birthmothers -- Fiction; Inheritance and succession -- Fiction; Thrillers (Fiction); Detective and mystery fiction; Audiobooks